A Systematic Evaluation of the Two-Component Systems Network Reveals That ArlRS Is a Key Regulator of Catheter Colonization by Staphylococcus aureus - Burgui, Saioa; Gil, Carmen; Solano, Cristina; Lasa, Iñigo; Valle, Jaione (Frontiers in Microbiology, 2018)
Two-component systems (TCS) are modular signal transduction pathways that allow cells to adapt to prevailing environmental conditions by modifying cellular physiology. Staphylococcus aureus has sixteen TCSs to adapt to the diverse microenvironments encountered during its life cycle, including host tissues and implanted medical devices. S. aureus is particularly prone to cause infections associated to medical devices, whose surfaces coated by serum proteins constitute a particular environment. Identification of the TCSs involved in the adaptation of S. aureus to colonize and survive on the surface of implanted devices remains largely unexplored. Here, using an in vivo catheter infection model and a collection of mutants in each nonessential TCS of S. aureus, we investigated the requirement of every TCS for colonizing the implanted catheter. Among the fifteen mutants in nonessential TCSs, the arl mutant exhibited the strongest deficiency in the capacity to colonize implanted catheters. Moreover, the arl mutant was the only one presenting a major deficit in PNAG production, the main exopolysaccharide of the S. aureus biofilm matrix whose synthesis is mediated by the icaADBC locus. Regulation of PNAG synthesis by ArlRS occurred through repression of IcaR, a transcriptional repressor of icaADBC operon expression. Deficiency in catheter colonization was restored when the arl mutant was complemented with the icaADBC operon. Instead, MgrA, a global transcriptional regulator downstream ArlRS that accounts for a large part of the arlRS regulon, was unable to restore PNAG expression and catheter colonization deficiency of the arlRS mutant. These findings indicate that ArlRS is the key TCS to biofilm formation on the surface of implanted catheters and that activation of PNAG exopolysaccharide production is, among the many traits controlled by the ArlRS system, a major contributor to catheter colonization.